DESIGN OF WORK AID TOOLS TO IMPROVE MAN POWER WORK POSTURE USING RULA METHOD (RAPID UPPER LIMB ASSESSMENT) PT.XYZ - Sudiarto, Arya Dika; Khofiyah, Nida An; Feriaty, Syarah Rizkia (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2025)
This research was conducted in the ACG-S Department with the object of observation of Man Power in the Wire Connection Soldering Stator Line 4B Process. With the aim of obtaining the value of Man Power's work posture and providing recommendations for improving work posture in the Wire Connection Soldering Process. To find out the data, the researcher used the Nordic Body Map (NBM) Questionnaire to find out subjective complaints from Man Power, then a work posture assessment was carried out using the Rapid Upper Limb Assessment (RULA) Method. The results of the Nordic Body Map (NBM) Questionnaire showed that 4 out of 6 Man Power complained of pain in the neck, back, shoulders, and waist areas, then from the results of the work posture assessment using the RULA method, a final score of 6 was obtained, which means that the Man Power's work posture position is at a high level (High) meaning that there is a high risk of Man Power getting Musculoskeletal Disorders (MSDs) and requiring posture improvement. Improvement of work posture is carried out by adding work aids, namely magnifying glasses and Poka Yoke Camera Soldering. After improving posture by adding work aids, the results of the work posture assessment using the RULA method obtained a final score of 3, which means that the Man Power work posture position after adding work aids is at a moderate level, which means that there is a moderate risk of Man Power getting Musculoskeletal Disorders (MSDs) and does not require action to improve body posture.